1990
DOI: 10.1002/ijc.2910460303
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and determinants of skin cancer in a high‐risk australian population

Abstract: In a Queensland community, we surveyed the incidence of basal-cell carcinoma (BCC) and squamous-cell carcinoma (SCC), and associated risk factors. In December, 1986, 2,095 residents were examined by dermatologists for skin cancer. Of these, 1,770 further participated in a follow-up postal survey in December, 1987, regarding all skin cancers in the preceding 2 years, and 87 reported being treated for skin cancer in the 2-year period between December 1985 and November 1987. The estimated annual incidence rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
156
2
12

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(180 citation statements)
references
References 13 publications
9
156
2
12
Order By: Relevance
“…This fact was expected and is consistent with the findings 15,24,26 registered in the literature demonstrating that sunburn is a risk factor for malignant melanoma but not for non-melanoma cancer. In a previous investigation in which they studied the sunburns of their patients quantitatively, Green et al 16 were only able to detect a discrete significance for non-melanoma skin cancer when the number of reported sunburns was of more than six episodes during the patient's life.…”
Section: Nonsignificant Risk Factorssupporting
confidence: 93%
See 3 more Smart Citations
“…This fact was expected and is consistent with the findings 15,24,26 registered in the literature demonstrating that sunburn is a risk factor for malignant melanoma but not for non-melanoma cancer. In a previous investigation in which they studied the sunburns of their patients quantitatively, Green et al 16 were only able to detect a discrete significance for non-melanoma skin cancer when the number of reported sunburns was of more than six episodes during the patient's life.…”
Section: Nonsignificant Risk Factorssupporting
confidence: 93%
“…Vitaliano and Urbach 34 in the USA, and Green and Battistutta 15 , in Australia, conducted studies of the risk factors by applying multiple conditional logistic regression analysis, which is a more adequate statistical model. Their studies referred to non-melanoma skin cancer in general and their results regarding BCC will be discussed below.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, cumulative lifetime sun exposure has a clearer effect on SCC than on BCC (Vitasa et al, 1990;Gafa et al, 1991). The studies that considered circumstance of exposure showed that sun exposure during work was associated more strongly with SCC than BCC (Green and Battistutta, 1990;Gafa et al, 1991). Exposure during nonworking activities has been studied rarely in non-melanocytic skin cancer and has not generally been quantified satisfactorily, thus failing to show clear results.…”
mentioning
confidence: 99%